Computational chemistry. Volume 8 : reviews of current trends - Leszczynski, Jerzy, 1949- (Singapore : World Scientific, 2003)
Chapter 1 of this volume provides an overview of the theoretical andnumerical aspects in the development of the polarizable continuummodel (PCM). Chapter 2 demonstrates a multiplicative scheme used toestimate the properties of two- and three-dimensional clusters from the properties of their one-dimensional components.
ch. 1. Computational modelling of the solvent effects on molecular properties / Roberto Cammi, Benedetta Mennucci and Jacopo Tomasi -- ch. 2. Electronic and nonlinear optical properties of 2-methyl-4-nitroaniline clusters / Maxime Guillaumea [and others] -- ch. 3. Ab initio calculations of the intermolecular nuclear spin-spin coupling constants / Magdalena Pecul and Joanna Sadlej -- ch. 4. Base polyad motifs in nucleic acids biological significance, occurrence in three-imensional experimental structures and computational studies / Michael Meyer and Jiirgen Siihnel -- ch. 5. Model calculations of radiation induced damage in DNA constituents using density functional theory / David M. Close -- ch. 6. Excited states of nucleic acid bases / M.K. Shukla and Jerzy Leszczynski.
Includes bibliographical references.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Chemistry -- Mathematics; Parallel computers; Ordinateurs parallèles.; SCIENCE -- Chemistry -- General; Chemistry -- Mathematics; Parallel computers